The red bandanna - Rinaldi, Tom (Viking, 2017)
Examines the life of Welles Crowther, a boy who grew up in Upper Nyack, New York and always had in his back pocket a red handkerchief his father had given him one Sunday before church. Crowther grew up and got a job on the 104th floor of the South Tower of the World Trade Center, and, according to witnesses, he died there saving others' lives while wearing that handkerchief.